CORPORATE NATIONALITY IN INTERNATIONAL INVESTMENT LAW - Aleksandrs Fillers (European Scientific Journal, ESJ, 2014)
International investments are common feature of globalized economy. Such investments need protection against arbitrary and discriminatory measures by the host state. International investment law, through a web of international bilateral and multilateral treaties, provides such protection. These treaties offer extremely generous guarantees to foreign investors. Each international investment treaty has its own scope of application. Many of them protect investments made by companies, incorporated under the laws of another Contracting State. The formal criterion of incorporation allows nationals of the host state or nationals of third states, not parties to the relevant treaty, benefiting from investment treaty protection, by incorporating companies in a Contracting State. In this article, author presents a short overview of arbitration practice, interpreting the corporate nationality requirement. The author argues that international investment treaties, determining corporate nationality by means of incorporation, must be applied literally, without requiring any additional links between the corporate entity in question and the place of incorporation.